Carmes Polytechnique, Housing in the Heart of Paris Energy renovation of a social housing estate in Paris - Horn, Christian (project baikal, 2017)
The architecture offices Atelier de la Seine and Rethink have been commissioned with the engineers Pouget Consultants by the social landlord Paris Habitat for the extensive renovation of a social housing estate in the historic centre of Paris. The estate has been built in 1930 and integrates a part of the former college of the Lombard build in the 17th century. It belongs to the social housing typology 'Habitations à Bon Marché (HBM)' constructed between1894 and 1949. This typology is generally characterized by its integration in its urban context and an apparent brick facade. The renovation project includes a focus on the reduction of the energy consumption. An important subject, as of the total number of 4.6 millions of social housing in France more than 50 % have been build before 1975 (before the first thermal regulation) and many are still considered energy-intensive.
Keywords: Paris Habitat; Paris; social housing; Habitations à Bon Marché; HBM; renovation; energy reduction